Control Pest of Leaf Caterpillars (Plutella xylostella) in Delima Rose Apples Using Soursop Leaf Extract (Annona muricata) (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The increasing of pesticide use is in line with the increasing number of pest populations. However, the use of pesticides causes various negative impacts on the environment (soil, water, and air) such as pesticide-resistant pests, perishing of useful insects which are non-target pesticides, and the use of pesticide which can even lead to poisoning and death in humans. One of the environmentally-safe techniques to control pests is chemical, by the use soursop leaf extract. This study aims to determine the most effective concentration of soursop leaf extract (Annona muricata) in controlling leaf caterpillar (Plutella xylostella) in delima rose apples. The research was carried out in the plantation area of rose apples in tempuran village, Demak. The research method employed experimental research. The study was conducted using Completely Randomized Design. The data were obtained using probit analysis of LC50. The most effective concentration of soursop extract (Annona muricata) on leaf caterpillars’ mortality was 75 ppm. Soursop leaf extract (Annona muricata) has been proven to influence rose apples leaf caterpillars’ mortality index. The LC50 value of soursop leaf extract was 75,16 mg/L. The result showed that soursop leaf extract (Annona muricata) is effective as a biopesticide material to control leaf caterpillar pest for delima rose apples.